1991
DOI: 10.3109/02699059109008095
|View full text |Cite
|
Sign up to set email alerts
|

Improving executive function disorders in brain-injured clients

Abstract: In 1983, Lezak described executive functioning as the ability to engage in independent, purposeful, self-directive and self-serving behaviour. Self initiation, problem-solving and self-monitoring or regulation of behaviour are important components of executive functioning. This paper presents the results of efforts to improve executive functioning in three areas: problem solving, self-initiation and self-regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 4 publications
2
37
0
1
Order By: Relevance
“…Our study demonstrated that restoring executive functions is possible. Rehabilitation of executive functions is usually based on compensatory techniques (Burke, Zenicus, Wesolowski & Doubleday, 1991;Cicerone & Wood, 1987;Lawson & Rice, 1989;von Cramon & Matthes-von Cramon, 1994). The main goal is to facilitate adaptation to disability rather than to rehabilitate the damaged function.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that restoring executive functions is possible. Rehabilitation of executive functions is usually based on compensatory techniques (Burke, Zenicus, Wesolowski & Doubleday, 1991;Cicerone & Wood, 1987;Lawson & Rice, 1989;von Cramon & Matthes-von Cramon, 1994). The main goal is to facilitate adaptation to disability rather than to rehabilitate the damaged function.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, people who make task failures may be helped through training in the use of external aids or compensatory strategies, such as checklists (e.g., see Burke et al, 1991). Robertson, Levine, and their colleagues have also achieved promising results with people with everyday disorganization problems using Goal Management Training and other methods (Robertson, 1996;Levine et al, 2000;Manly et al, 2002).…”
Section: Simplified Multiple Errands Testmentioning
confidence: 96%
“…Examples of inhibitory control include ignoring competing information while performing a working memory task (Hasher & Zacks, 1988), withholding a prepotent or dominant response (Logan, 1994), or ignoring irrelevant visual information while processing target stimuli (Eriksen & Eriksen, 1974). Given the countless sources of interference encountered on a moment-by-moment basis, intact inhibitory control is essential for navigating and interacting effectively with the environment (Burke, Zencius, Wesolowski, & Doubleday, 1991). Whereas a number of studies have reported significant impairments on measures of inhibitory control in individuals with ASD (e.g., Geurts, Verte, Oosterlaan, Roeyers, & Sergeant, 2004;Minshew, Luna, & Sweeney, 1999;Ozonoff, Strayer, McMahon, & Fillouz, 1994), others have failed to find a difference between individuals with ASD and their control counterparts (e.g., Eskes, Bryson, & McCormick, 1990;Griffith, Pennington, Wehner, & Rogers, 1999;Ozonoff & Jensen, 1999;Ozonoff & Strayer, 1997).…”
Section: Introductionmentioning
confidence: 99%